2014
DOI: 10.1186/2251-6581-13-72
|View full text |Cite
|
Sign up to set email alerts
|

Effects of educational intervention based on PRECEDE model on self care behaviors and control in patients with type 2 diabetes in 2012

Abstract: BackgroundDiabetes is a chronic disease and its control requires essential change in patients' life style. The aim of this study was survey of effects of educational intervention based on PRECEDE Model on self care behaviors and control in patients with type 2 diabetes.MethodsThis was a quasi-experimental study carried out in 78 patients with type 2 diabetes who have referred to Minoodasht clinic of diabetes. The educational program has been designed according to the PRECEDE Model. Prior to perform the educati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
25
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 10 publications
10
25
0
2
Order By: Relevance
“…The results of this study agree with those reported by Dizaji et al, 10 showing an improvement in the know ledge score of patients with diabetes after the implementation of an educational intervention program. Therefore, it can be concluded that there was a positive impact on the knowledge of patients with diabetes.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results of this study agree with those reported by Dizaji et al, 10 showing an improvement in the know ledge score of patients with diabetes after the implementation of an educational intervention program. Therefore, it can be concluded that there was a positive impact on the knowledge of patients with diabetes.…”
Section: Discussionsupporting
confidence: 93%
“…Behavioral change was one of the most difficult steps in the edu cational process, despite providing educational intervention to people for three months. 10 A study by Skarbek, 11 also mentioned that family support would help people with type-2 DM increase their self-efficacy in self-managing actions. A study by Mayberry and Osborn mentioned that instrumental support was the most common form of family support.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Matin et al, education based on the PRECEDE model had promoted the elderly's attitudes 33 . The findings of this study are consistent with those of other studies 34,35,36,37 .…”
Section: Variable/groupsupporting
confidence: 94%
“…Given that one of the basic tools in changing a patient’s lifestyle is the presence of patient education programs as a part of the care system [14,15], ongoing training is regarded as an essential part of the monitoring and treatment of high blood pressure and might need to be repeated or modified in order to address changing circumstances and patient conditions [3,16]. The importance of training programs depends on their effectiveness; however, in the presence of appropriate theoretical support along with basic health needs, the effectiveness of these programs is greater [17].…”
Section: Introductionmentioning
confidence: 99%